Revitalisasi Inklusif Jalan Panggung Surabaya dengan Pendekatan Urban Heritage Street - Ainin Bashiroh; Fitriyanti Ulul Azmi, Ade; Sarasanty, Diah (Lembaga Pengembangan Kinerja Dosen, 2025)
The revitalization of urban heritage areas in Indonesia, exemplified by Panggung Street in Surabaya, faces multifaceted challenges encompassing the preservation of historical character, socio-economic enhancement, and the creation of inclusive public spaces. Current revitalization efforts often misalign with the area’s authentic features such as inappropriate facade treatments while neglecting accessibility for vulnerable groups and failing to foster effective collaboration among stakeholders. This study employs a descriptive qualitative case study approach, synthesizing field observations, in-depth interviews with local actors, comprehensive literature reviews, and precedent analyses of Braga Street in Bandung and heritage zones in Malacca. Data were analyzed using SWOT and root cause analysis to identify systemic barriers and leverage opportunities, while comparative-historical interpretation contextualized Surabaya’s urban identity. Triangulation ensured methodological rigor and validity. The research culminates in a holistic revitalization framework emphasizing three key strategies: restoration of authentic architectural features, including original colors and ornamentation, enhancement of inclusive infrastructure, such as accessible pedestrian pathways and universal signage and active community participation through workshops and cultural initiatives like the Kya-Kya night market. This integrated approach not only preserves the area’s historical integrity but also fosters social cohesion, economic vitality, and collective pride. The study demonstrates that combining heritage conservation with inclusive design principles can transform urban spaces into dynamic, accessible, and sustainable environments. The findings offer valuable insights for other Southeast Asian cities facing similar heritage revitalization challenges.